Jumlah Anakan Maksimum dan Produktif Genotipe Padi Sawah Perbaikan Varietas Ciherang di Desa Belading Kecamatan Sabak Auh Kabupaten Siak Provinsi Riau - Supriadi Widodo; Gunawan Tabrani; Isnaini Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study discusses the potential of rice paddy lines to improve the Ciherang variety as a new variety approved in Riau based on the number of maximum and productive tillers. Research has been carried out in the fields belonging to the farmers of Belading Village, Sabak Auh Subdistrict, Siak Regency, Riau Province. The research done in experiment of a randomized block design (RBD) of 12 rice plant genotypes consisting of 10 repair lines of Ciherang variety and 2 comparable varieties, namely Ciherang and Inpari 33 varieties. Genotypes were planted in one rice field divided into 4 groups according to the direction of water direction irrigation. The observated were maximum and productive amount tiller. The data were analyzed for its variance and differences in the mean of each genotype were calculated by Duncan's New Multiple Range Test (DNMRT) at 5% level using SAS software version 16.0. The relationship between maximum and productive tillers saw in regression and correlation. The results showed 12 genotypes were significant to number of maximum and productive tillers. The lines G1, G2, G3, G4, G5, G7, G8, and G10 were developed as candidates for new varieties collected in Riau based on their maximum and productive tillers. The potential of the G9 strain as a new variety candidate in Riau is better than the lines G1, G2, G3, G4, G5, G7, G8, and G10 based on the number and productive tillers. Keywords: Genotypes, comparison varieties, maximum tillers, productive tillers